Stimulation of the insulin/mTOR pathway delays cone death in a mouse model of Retinitis Pigmentosa - Punzo, Claudio (2008)
Retinitis Pigmentosa (RP) is an incurable retinal disease that leads to blindness. One puzzling aspect concerns the progression of the disease. While most mutations that cause RP are in rod photoreceptor (PR) -specific genes, cone PRs die as well. To understand the mechanism of non-autonomous cone death, four mouse models harboring mutations in rod-specific genes were analyzed. Changes in the insulin/mTOR pathway that coincided with the activation of autophagy during the period of cone death were found. We thus either increased or decreased the insulin level and measured the survival of cones in one of the models. Mice treated systemically with insulin had prolonged cone survival, while depletion of endogenous insulin had the opposite effect. These data suggest that the non-autonomous cone death in RP could, at least in part, be due to the starvation of cones.